PENGARUH STRES KERJA DAN KONDISI FISIK KERJA TERHADAP KINERJA DOSEN DAN TENAGA KEPENDIDIKAN PADA SEKOLAH TINGGI ILMU EKONOMI AMA SALATIGA - Edi Murgijanto (Among Makarti, 2019)
AbstrakHuman resources as organizational assets are very decisive in the success of organizations including the STIE AMA Salatiga. The participation of the lecturers and education staff cannot be released in order to achieve the stated goals. Lecturers and education staff who are working require adequate physical work conditions and not high levels of stress to be able to perform better. The study was conducted to determine the effect of work stress and physical work conditions on the performance of lecturers and education staff at the AMA Salatiga College of Economics. The results of the study are expected to be an input for STIE AMA Salatiga in taking policies in an effort to improve the performance of lecturers and education staff, and are expected to have an impact on achieving the Function, Vision, Mission and Objectives of STIE AMA Salatiga. Based on the results of data analysis, researchers can draw conclusions about the effect of work stress and physical work conditions on the performance of lecturers and education staff at STIE AMA Salatiga as follows: The results of the validity test and reliability test show that each item statement and each research variable are declared valid and reliable. While the results of the partial test of work stress variables do not have a significant effect on the performance variables, while the physical condition variables work significantly influence the performance variables. Then simultaneous testing of work stress variables and physical conditions of work has a significant effect on performance variables. The coefficient of determination (R Square) is 0.20, this means that the independent variables of work stress and physical conditions of work can explain the dependent variable of performance by 20% and the remaining 80% explained by other factors not examined. Keywords : Stres Kerja, Kondisi Fisik Kerja, Kinerja